MANUFACTURING EQUIPMENT FOR BRUSH PLATING TECHNOLOGY USING FOR THE RESTORATION OF ABRADED PARTS OF MACHINES - Dư, Đào Khánh (Vietnam Journal of Science and Technology, 2012)
SUMMARYSince brush plating technology does not use a plating bath and it uses an anode moving directly on the surface of the plating parts, this technology can be used to restore surfaces of machine parts at defective areas due to either abrasion caused by operation or deficient dimensions caused by incorrect machining. As a result, this plating method can bring considerable economic and technological effects. Specification of brush plating technology also requires the most compatible equipment, particularly the plating current source. Producing the current source according to the principles of phase opposition, phase rectification, and the combination of both will allow the equipment to have a strong plating load up to 100 A and 200 A with a voltage that can be stably controlled to ensure that the brush plating process obtains high quality.